a-amylase from white pitaya Hylocereus undatus L. peel: optimization of extraction using full factorial design - Shad, Zahra; Mirhosseini, Hamed; Moteshakeri, Mahsa; Sanjabi, Mohammad Reza; Meor Hussin, Anis Shobirin (Kemerovo State University, 2021)
Introduction. Amylase is a significant enzyme with numerous commercial applications, which is largely used to convert starches into oligosaccharides. Extraction of amylase from plant by-products or cheap sources is cost-effective. Annually, pitaya fruit juice industry produces huge amounts of peels that could be utilized as an alternative source in enzyme production industry. The work aimed to examine and optimize extraction process. Study objects and methods. In this study, we investigated parameters of extraction to optimize the process, as well as activity of α-amylase from white pitaya fruit (Hylocereus undatus L.) peel. For this purpose, a two-level full factorial design was applied. Three variables, namely the pH of sodium phosphate buffer (X1, 4.5–7.5), mixing time (X2, 1–3 min), and a sample-to-buffer ratio (X3, 1:3–1:5), were used to identify significant effects and interactions within the samples. Results and discussion. The results demonstrated that the buffer pH had the most significant (P ≤ 0.05) effect on total amylase activity. Based on full factorial design analysis, we revealed the optimal conditions for amylase enzyme extraction ‒ pH of 6, mixing time of 2 min, and a sample-to-buffer ratio of 1:4. Lower and higher values influenced adversely on specific activity of amylase. Conclusion. Optimization increased the enzyme specific activity by a factor of 4.5. Thus, pitaya peel could be used in different industries as a rich natural α-amylase source.